Anisotropic Excitation Polarization Response from a Single White Light‐Emitting β‐NaYF4:Yb3+, Pr3+ Microcrystal. Issue 43 (6th September 2019) - Yang, Dandan; Peng, Zixing; Zhan, Qiuqiang; Huang, Xiongjian; Peng, Xingyun; Guo, Xin; Dong, Guoping; Qiu, Jianrong
Abstract: Precise knowledge about optical and structural performance of individual rare earth (RE)‐doped particles is extremely important for the optimization of luminescent particles and for fully exploiting their capability as multifunctional probes for interdisciplinary applications. In this work, optical and structural anisotropy of individual particles through RE‐doped single fluoride microcrystals with controllable morphology is reported. Unique luminescent phenomena, for example, white light‐emission from Pr 3+ at single particle level and different photoluminescent spectra variation dependence on excitation polarization orientation at different excitation direction are observed upon excitation with a 980 nm linearly polarized laser. Based on the analysis of local site symmetry and electron cloud distribution of REs in hexagonal structure by density functional theory calculations, an exciting mechanism of excitation polarization response anisotropy is given for the first time, providing a guidance for emission polarization simultaneously. The structural anisotropy is presented in Raman spectra with obvious differing Raman curves, revealing the reason why there are differences between powder groups. Taking advantage of anisotropic crystals, potential applications in microscopic multi‐information transportation are suggested for the optical and structural performance anisotropy from RE‐doped fluoride single nano/microcrystals to ordered nano/microcrystal arrays, such as local rate probing in a flowing liquid. Abstract : Anisotropic white light‐emitting β‐NaYF4 :Yb, Pr microcrystals are prepared for new insights into optical and structural anisotropy in individual particles. Different excitation polarization responses and Raman scattering modes observed in different excitation configurations clearly present the optical and structural anisotropy of as‐prepared microcrystals, and the corresponding mechanisms are discussed in detail, suggesting the importance of investigation of single particles.